Pengaruh Leverage, Likuiditas dan Ukuran Perusahaan Terhadap Profitabilitas pada Perusahaan Sub Sektor Tambang - Bhernike Rismayora Tambunan; Misa Yojana Sari Saragih; Deasy Arisandy Aruan; Frenky Situmorang (IPM2KPE, 2023)
The aim of this research is to determine the effect of leverage, liquidity and company size on profitability in mining sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The analytical method of this research is to use multiple regression analysis with the SPSS Version 22.0 application. The approach used in this research is a quantitative approach. The results of this research show that Leverage has a significant effect on Profitability, Liquidity has no significant effect on Profitability and Size has no significant effect on Profitability. The conclusion is that DER, Current Ratio, Size have a significant effect on profitability in mining sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Keywords: Current Ratio, Debt To Equity Ratio, Return On Assets, Size